Morphogenesis of the Sign - Piotrowski, David (Lecture Notes in Morphogenesis,, 2018)
This book develops a morphodynamical approach to linguistic and sign structures as an integrated response to multilevel and interrelated problems in semiolinguistic research. More broadly, the content is linked to the realities of living speech through a connection (via the concept of diacriticity) with the Merleau-Pontian phenomenology, and beyond the formal determinations of a semiolinguistic system and its calculus. Such problems are mainly epistemological (concerning the nature and legitimate scope of semiolinguistic knowledge), empirical (concerning the observational device and the data's composition), and theoretical (regarding the choice of a conceptual and formalized explicative frame). With regard to theory, the book introduces a morphodynamical architecture of linguistic signs and operations as a suitable mathematization of Saussurean theory. The Husserlian phenomenological signification of this formal apparatus is then established, and, from an empirical standpoint, its compatibility with neurobiological experimental results is discussed.